An Evolutionarily Conserved Role for Polydom/Svep1 During Lymphatic Vessel Formation. Issue 8 (14th April 2017) - Karpanen, Terhi; Padberg, Yvonne; van de Pavert, Serge A.; Dierkes, Cathrin; Morooka, Nanami; Peterson-Maduro, Josi; van de Hoek, Glenn; Adrian, Max; Mochizuki, Naoki; Sekiguchi, Kiyotoshi; Kiefer, Friedemann; Schulte, Dörte; et al.
Abstract : Rationale: : Lymphatic vessel formation and function constitutes a physiologically and pathophysiologically important process, but its genetic control is not well understood. Objective: : Here, we identify the secreted Polydom/Svep1 protein as essential for the formation of the lymphatic vasculature. We analyzed mutants in mice and zebrafish to gain insight into the role of Polydom/Svep1 in the lymphangiogenic process. Methods and Results: : Phenotypic analysis of zebrafish polydom / svep1 mutants showed a decrease in venous and lymphovenous sprouting, which leads to an increased number of intersegmental arteries. A reduced number of primordial lymphatic cells populated the horizontal myoseptum region but failed to migrate dorsally or ventrally, resulting in severe reduction of the lymphatic trunk vasculature. Corresponding mutants in the mouse Polydom / Svep1 gene showed normal egression of Prox-1 + cells from the cardinal vein at E10.5, but at E12.5, the tight association between the cardinal vein and lymphatic endothelial cells at the first lymphovenous contact site was abnormal. Furthermore, mesenteric lymphatic structures at E18.5 failed to undergo remodeling events in mutants and lacked lymphatic valves. In both fish and mouse embryos, the expression of the gene suggests a nonendothelial and noncell autonomous mechanism. Conclusions: : Our data identify zebrafish and mouse Polydom/Svep1 as essential extracellular factors for lymphangiogenesis. Expression of the respective genes by mesenchymal cells in intimate proximity with venous and lymphatic endothelial cells is required for sprouting and migratory events in zebrafish and for remodeling events of the lymphatic intraluminal valves in mouse embryos. Abstract : Supplemental Digital Content is available in the text.